If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + 3x = -3 + 8 Combine like terms: -3 + 8 = 5 -2 + 3x = 5 Solving -2 + 3x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 3x = 5 + 2 Combine like terms: -2 + 2 = 0 0 + 3x = 5 + 2 3x = 5 + 2 Combine like terms: 5 + 2 = 7 3x = 7 Divide each side by '3'. x = 2.333333333 Simplifying x = 2.333333333
| 2x+8=-48-8x | | x^2+3x=65.7 | | -4+11n-15y-n= | | 29+29x=15+31x | | -9(7x+8)=-198 | | 4y+5+2y=13 | | -9(7+8)=-198 | | -3(x+9)+2x=5(x+10)-5 | | 29+29x=15+3x | | 2(r+5)=4r | | (10x-1)+(5x+6)= | | 275=60x+25(4) | | 9x^4+16x^3-76x^2-8x+32=0 | | 3(b+2)=2(c+3) | | 14x+12y=178 | | 3(c-2)=(c+3) | | 6x^2y-2xy^2+3xy-5= | | 4x^2+3y^2-16x+12y+16=0 | | -x^3+6x^2-11x+6=0 | | -5x+27=3y | | n=4.7 | | sqrt(8x+1)+sqrt(3x-5)=sqrt(7x+4)+sqrt(2x-2) | | x=16+-9(2) | | 3x+2y=7whatisx | | 6x-8=20x-22 | | 3(16+-9y)+8y=10 | | (5b-5d)(5b+4d)= | | (4x^2)+(3y^2)-16x+12y+16=0 | | x=16+-9(1) | | x+2y+2z-5=0 | | 7+3(2+x)=28 | | 5y+3y^2=2 |